A high-resolution record of early rift development and tectonic, sedimentary and environmental conditions in an active rift basin: IODP MSP drilling in the Corinth Rift, Greece (Expedition 381) - Lisa C. McNeill; Donna J. Shillington; Jeanine Ash; Gareth D.O. Carter; Richard E.Ll. Collier; Aleksandra Cvetkoska; Paula Diz; Mai-Linh Doan; Jeremy D. Everest; Natacha Fabregas; Eugenia Fatourou; Mary Ford; et al. (Marine Geology, 2026)

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Numerical evaluation of corrosion effects on the flexural behaviour of post-tensioned concrete bridge girders with defective grouting - Simone Galano; Daniele Losanno; Fulvio Parisi (Engineering Structures, 2025)

The early Aptian marine stratigraphic record in the interior of Gondwana: New insights from the Araripe Basin, Northeastern Brazil - Henrique Parisi Kern; Jorge Villegas-Martín; Gerson Fauth; Fernanda Luft-Souza; Oscar Strohschoen; Lilian Maia Leandro; Alessandra Santos; Mauro Daniel Rodrigues Bruno; Edna de Jesus Francisco Tungo; Marcos Antonio Batista dos Santos Filho; Daiane Ceolin; Simone Baecker-Fauth; et al. (Marine and Petroleum Geology, 2025)

Assessing the activity and stability of Cu2O/SnO2-based gas diffusion electrodes for the CO2 conversion in different electrolytes: Bicarbonate vs. Ionic Liquid/Acetonitrile - Federica Zammillo; Hilmar Guzmán; Daniela Polino; Roger Miró; Alberto Lopera; Emmanuele Parisi; Alessia Fortunati; Maddalena Zoli; Elena Simone; Nunzio Russo; Mariajose López-Tendero; Miriam Díaz de los Bernardos; et al. (Chemical Engineering Journal, 2025)

A crystal engineering approach for rational design of curcumin crystals for Pickering stabilization of emulsions - Giulia Del Duca; Emmanuele Parisi; Fiora Artusio; Eleonora Calì; Silvia Fraterrigo Garofalo; Chiara Rosso; Valentina Cauda; Michele R. Chierotti; Elena Simone (Food Research International, 2024)

Valorization of pyrolytic plastic-derived char for adsorption of wastewater contaminants: a kinetic and thermodynamic investigation - F. Barracco; E. Parisi; G. Pipitone; E. Simone; S. Bensaid; D. Fino (International Journal of Environmental Science and Technology, 2024)
The sustainable management of plastic waste is one of the challenges of our time due to the high percentage of landfilling. One of the strategies is its thermal treatment via pyrolysis, but it is associated with the production of a char, necessitating a proper valorization pathway. In this work, we investigated for the first time the use as adsorbent of a real plastic-derived char obtained as such from a pyrolysis pilot plant. This is a novel approach with respect to literature, where the char is typically obtained as desired product. The adsorbent was characterized via several techniques, and methylene blue was chosen as representative contaminant of wastewater. The inorganic component (80 wt.%) was mainly associated with the presence of rod-like structures, rich in Si, while the organic fraction showed the occurrence of aromatic components. Under the thermodynamic point of view, Langmuir isotherm effectively fitted the experimental data ( R 2 = 0.98), while the kinetic results were well described by a pseudo-second-order law ( R 2 > 0.99). The negative Gibbs free energy highlighted that the adsorption process was spontaneous, and the enthalpy change (∆ H 0 = 7.18 kJ/mol) revealed the endothermic nature of the process, in a range characteristic of physisorption phenomena. Overall, this study highlights that a low-value char, derived from a real plastic waste, can be a promising valuable alternative to expensive adsorbents thanks to its adsorption capacity of 5.8 mg/g without prior activation treatments, hence being a starting point for the development of a holistic approach in plastic waste management.

Influence of strand rupture on flexural behavior of reduced-scale prestressed concrete bridge girders with different prestressing levels - Daniele Losanno; Simone Galano; Fulvio Parisi (Engineering Structures, 2024)

Multi-locus sequence typing and in vitro antimicrobial resistance of equine Streptococcus equi subspecies zooepidemicus strains - Francesca Paola Nocera; Loredana Capozzi; Domenico Simone; Francesca Pizzano; Valentina Iovane; Angelica Bianco; Antonio Parisi; Luisa De Martino (Veterinary Research Communications, 2024)

Progressive collapse fragility of substandard and earthquake-resistant precast RC buildings - Martina Scalvenzi; Simone Ravasini; Emanuele Brunesi; Fulvio Parisi (Engineering Structures, 2023)

Ask the shark: blackmouth catshark (Galeus melastomus) as a sentinel of plastic waste on the seabed - Alice Sbrana; Alessandro Cau; Davide Cicala; Simone Franceschini; Tommaso Giarrizzo; Maria Flavia Gravina; Alessandro Ligas; Giulia Maiello; Marco Matiddi; Antonio Parisi; Paolo Sartor; Mario Sbrana; et al. (Marine Biology, 2022)
The presence of plastic waste in the marine environment has driven the scientific community to make significant efforts to study and mitigate its possible effects. One of the critical aspects is to determine if and how an increase in ingestion events may occur as a result of the accumulation of plastic waste on the seabed. In this study, G. melastomus is examined for its ability to indirectly provide information on the amount of macroplastics accumulating on the seafloor. Plastic ingestion is explored by describing the feeding habits of the species, which have the potential to provide very useful information regarding biological or ecological issues. The diet of G. melastomus mainly consisted of cephalopods, bathypelagic fishes, and decapod crustaceans, increasing in diversity during growth. The generalist-opportunistic feeding behaviour of this species leads to the incidental ingestion of plastic particles ( N = 47, with a mean (± SD) of 1.47 ± 0.28 per specimen) which can be indirectly associated to the presence of macroplastics on the seafloor. Indeed, our results indicate a significant relationship between the amount of macroplastics present on the seabed and the frequency of ingestion of plastic particles by blackmouth catshark. We propose G. melastomus as an excellent candidate for developing a valid monitoring strategy for the presence of plastics on the seabed, as requested by the EU Marine Strategy Framework Directive.

Defend as You Can, React Quickly: The Effects of the COVID-19 Shock on a Large Fishery of the Mediterranean Sea - Tommaso Russo; Elena Catucci; Simone Franceschini; Lucio Labanchi; Simone Libralato; Evelina Carmen Sabatella; Rosaria Felicita Sabatella; Antonio Parisi; Fabio Fiorentino (Frontiers in Marine Science, 2022)
This paper presents an analysis of the effect of SARS-CoV-2 coronavirus pandemic and related restrictive measures on the activity of the Italian fleet of trawlers, which represents one of the most important fisheries in the Mediterranean Sea. We integrated multiple sources of information including: (1) Fleet activity data from Vessel Monitoring System, the most important satellite-based tracking device; (2) vessel-specific landing data disaggregated by species; (3) market and economic drivers affecting the effort variation during the lockdown and in the related fishing strategies; (4) monthly landings of demersal species in the main Italian harbors. These data sources are combined to: (1) Assess the absolute and relative changes of trawling effort in the geographical sub-areas surrounding the Italian coasts; (2) integrate and compare these changes with the market and economic drivers in order to explain the observed changes in fishing effort and strategy; (3) analyze the changes of the fishing effort on the Landing-per-unit-effort (LPUE) in order to further understand the strategy adopted by fishers during this crisis and to infer the potential consequence for the different stocks. The results provide an overview of the effects of the “COVID-19 shock,” in terms of fishing activity and socio-economic drivers, demonstrating that the consequences of the pandemic have been very varied. Although the COVID-19 shock has caused a marked overall reduction in activity in the first semester of 2020, in some cases the strategies adopted by fishermen and the commercial network linked to their activity have significantly reduced the impact of the emergency and taken back catch and effort to levels similar to those of previous years. These results could provide insights for management measures based on temporal stops of fishing activities. In particular, if no limits to the fishing effort after the restart of fishing activities are adopted, the benefits of fishing pressure reduction on fishery resources could be nullified. On the other hands, when fishing activities restart, and in the absence of catch control, effort tends to increase on coastal bottoms characterized by greater abundance of resources and longer effective fishing time.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Nutritional Quality, Physical Properties and Lipid Stability of Ready-to-cook Fish Products are Preserved during Frozen Storage and Oven-cooking - Yara Husein; Giulia Secci; Simone Mancini; Bruno Zanoni; Giuliana Parisi (Journal of Aquatic Food Product Technology, 2020)

Predicting Fishing Footprint of Trawlers From Environmental and Fleet Data: An Application of Artificial Neural Networks - Tommaso Russo; Simone Franceschini; Lorenzo D’Andrea; Michele Scardi; Antonio Parisi; Stefano Cataudella (Frontiers in Marine Science, 2019)

Simulating the Effects of Alternative Management Measures of Trawl Fisheries in the Central Mediterranean Sea: Application of a Multi-Species Bio-economic Modeling Approach - Tommaso Russo; Lorenzo D'Andrea; Simone Franceschini; Paolo Accadia; Andrea Cucco; Germana Garofalo; Michele Gristina; Antonio Parisi; Giovanni Quattrocchi; Rosaria Felicita Sabatella; Matteo Sinerchia; Donata M. Canu; et al. (Frontiers in Marine Science, 2019)

Trends in Effort and Yield of Trawl Fisheries: A Case Study From the Mediterranean Sea - Tommaso Russo; Paolo Carpentieri; Lorenzo D’Andrea; Paola De Angelis; Fabio Fiorentino; Simone Franceschini; Germana Garofalo; Lucio Labanchi; Antonio Parisi; Michele Scardi; Stefano Cataudella (Frontiers in Marine Science, 2019)

Safety, efficacy and immunogenicity of switching from innovator to biosimilar infliximab in patients with spondyloarthritis: a 6-month real-life observational study - Maurizio Benucci; Francesca Li Gobbi; Francesca Bandinelli; Arianna Damiani; Maria Infantino; Valentina Grossi; Mariangela Manfredi; Simone Parisi; Enrico Fusaro; Alberto Batticciotto; Piercarlo Sarzi-Puttini; Fabiola Atzeni; et al. (Immunologic Research, 2017)

Spring thermal resources for grapevine in Kőszeg (Hungary) deduced from a very long pictorial time series (1740–2009) - Simone Gabriele Parisi; Moreno Mauro Antoniazzi; Gabriele Cola; Lorenzo Lovat; Luigi Mariani; Giacomo Morreale; Kiss Zoltan; Antonio Calò (Climatic Change, 2014)

Space and time behavior of climatic hazard of low temperature for single rice crop in the mid latitude - Luigi Mariani; Simone Gabriele Parisi; Gabriele Cola (International Journal of Climatology, 2009)
Rice is a crop of tropical origin and therefore very sensitive to low temperatures, particularly during the crucial phase of floral differentiation. A World survey on climatic hazard of low temperatures during this phase was carried out on the basis of National Centers for Environmental Prediction (NCEP) reanalysis temperature data at 850 hPa. The spatial behavior of risk in analysed areas shows high risk for Australia, moderate one for Europe, South America and East Asia, whereas a very low or null risk is shown for North Africa, South Brazil, Iran, Korea and Louisiana. Results show that the level of risk for many regions of the Boreal hemisphere is substantially lowered after the breakpoint of 1981, whereas a more stable situation of risk is observed in the Austral one and particularly in Australia. A global map of risk was also produced and possible limitations of the selected approach are finally discussed. Copyright © 2008 Royal Meteorological Society